2014
DOI: 10.1186/1471-2180-14-68
|View full text |Cite
|
Sign up to set email alerts
|

pZMO7-Derived shuttle vectors for heterologous protein expression and proteomic applications in the ethanol-producing bacterium Zymomonas mobilis

Abstract: BackgroundThe ethanol-producing bacterium Zymomonas mobilis has attracted considerable scientific and commercial interest due to its exceptional physiological properties. Shuttle vectors derived from native plasmids have previously been successfully used for heterologous gene expression in this bacterium for a variety of purposes, most notably for metabolic engineering applications.ResultsA quantitative PCR (qPCR) approach was used to determine the copy numbers of two endogenous double stranded DNA plasmids: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…For pZP605 even after 50 generations without antibiotic selection, almost all cells in the population expressed mCherry. This confirms the observation by So et al (2014) who reported that their pZMO7-based shuttle vector was stable for at least 50 generations. pZP605, unlike the derivative pZ7C (So et al, 2014), does not carry any of the genes of pZMO7 other than the putative replication-associated gene.…”
Section: Determination Of Plasmid Stabilitysupporting
confidence: 91%
“…For pZP605 even after 50 generations without antibiotic selection, almost all cells in the population expressed mCherry. This confirms the observation by So et al (2014) who reported that their pZMO7-based shuttle vector was stable for at least 50 generations. pZP605, unlike the derivative pZ7C (So et al, 2014), does not carry any of the genes of pZMO7 other than the putative replication-associated gene.…”
Section: Determination Of Plasmid Stabilitysupporting
confidence: 91%
“…The cell pellets were treated at 95°C for 10 min followed by immediate freezing at −20°C and used as the templates for quantitative (real time) PCR analyses. 23,24) DNA concentrations were determined using a Nanodrop 2000 spectrophotometer (Thermo Scientific, DE, USA). qPCR was performed using an iQ5 Real-time PCR System (Bio-Rad Laboratories, Inc., Hercules, CA, USA) with reaction mixtures (total volume 20 μL) containing 10 μL 2 × TaKaRa SYBR Green Real-Time PCR Master Mix (Takara, Dalian, China), 1.5 μL forward and reverse primers (10 μM stock), and 1 μL of sample.…”
Section: Plasmid Copy Number Determination By Quantitative Real-time mentioning
confidence: 99%
“…E. coli-Z. mobilis shuttle vectors, which contain replicons from E. coli and from Z. mobilis native plasmids, are currently the most popular plasmid-based expression systems (So et al 2014) (Fig. 3A).…”
Section: Genetic Engineering Tools Available For Z Mobilismentioning
confidence: 99%